PENGARUH KERJA SAMA TIM DAN ORGANISASI PEMBELAJARAN TERHADAP KINERJA KARYAWAN PT SELIM ELEKTRO - Khaerunnisa; Bambang Riono, Slamet; Dwi Harini (Lembaga Pengembangan Kinerja Dosen, 2022)
The development of industrial enterprises today is increasingly demanding quality human resources. PT Selim Elektro is a company engaged in the assembly of electronic cables that produce wire harnesses, especially in the Brebes region. The problem that arises today at PT Selim Elektro is about the performance of employees who have not been optimal. Employee performance is the main focus that must be improved immediately so that work targets are achieved and increased. The success of an enterprise cannot be achieved if it relies solely on individual efforts, but requires cooperation between employees and the organization of learners within the company. The purpose of this study was to determine how much influence teamwork and learning organizations have on the performance of PT Selim Elektro employees. This research uses quantitative methods. The method of sampling in a random way, as well as the number of samples were established by the Slovin formula, a total of 91 employees. The data analysis tools in this study used the analysis of t-test tests, F tests, and multiple linear regression tests, which were tested by instruments with previous validity and reliability tests. The results of this study show that teamwork and learning organizations can affect the improvement of the performance of PT Sellim Elektro employees. The amount of influence of teamwork variables and learning organization variables on employee performance variables was 54.3%, and the rest by other variables not examined